Institutional Literacy and Libraries: Addressing Library Anxiety with a Personal Librarian Program - Doerksen, Brad (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
This article considers institutional literacy as a lens through which to consider causes of library anxiety and the development of library programs. Institutional literacy is the ability to read and engage with the ways of being and doing that are -- often invisibly -- embedded into institutions of all kinds. This article posits that the ability of library users to confidently engage with library services is in part predicated on the level of institutional literacy these users have, both in the institution of the library itself and any larger host institution – such as a university.A setting such as a university requires a range of literacies, and those developing programs and services in such settings should not assume new and potential library users already have developed these literacies. While librarians are accustomed to considering information literacy as their contribution to this matrix, unfamiliar institutional literacy practices can present obstacles to new library users becoming information literate.A comparison of research on the effects of a lack of institutional literacy and research into library anxiety demonstrates parallels that suggest that low levels of institutional literacy are a contributing factor to library anxiety, creating one of the aforementioned obstacles. Acting as institutional literacy mediators is one way library workers can respond to this challenge. The article concludes with a description of how the theoretical lens thus developed was used to inform the development of a personal librarian program at the University of Regina, in part by positioning librarians as institutional literacy mediators.